Management of oligo-metastatic and oligo-recurrent cervical cancer: A pattern of care survey within the EMBRACE research network. (February 2021) - Chopra, Supriya; Mangaj, Akshay; Sharma, Alisha; Tan, Li Tee; Sturdza, Alina; Jürgenliemk-Schulz, Ina; Han, Kathy; Huang, Fleur; Schmid, Maximilian P.; Fokdal, Lars; Chargari, Cyrus; Diendorfer, Tamara; et al.
Highlights: The survey results described in the manuscript captures the heterogeneity in the clinical practice of oligometastatic and oligorecurrent cervical cancer. This survey will help to define the role of radiation therapy in oligometastatic and oligorecurrent cervical cancer. This survey highlights the desire of radiation oncologists over the globe to practice stereotactic radiation therapy in oligometastatic disease and will help to plan future clinical trials. Abstract: Background: In the metastatic or recurrent cervical cancer, systemic chemotherapy constitutes the main treatment. Though there is an increasing use of high dose external radiation and brachytherapy in the metastatic setting, no consensus exists. Methods: A 17-item survey was designed with additional case-based questions to explore present management of oligo-metastatic and oligo-recurrent cervix cancer within EMBRACE research group participating sites. The questions were designed to elicit prevailing practices in the management of de-novo oligo-metastasis and oligo-recurrent setting after completing the primary treatment of cervix cancer. The survey was sent electronically with two rounds of email reminders to respond over a 2-week survey period. The online survey was designed such that it was mandatory to complete all questions. The responses were recorded and results were summarized as proportions and summary statistics were generated. Results: Twenty-two centers responded to this survey. A majority (90%) of respondents reported a low incidence of de-novo oligo-metastatic cervical cancer in their practice (<5%), with a higher proportion of patients with oligo-recurrence after completing primary treatment (5–10%). All responding sites preferred to treat pelvic disease in the de-novo oligo-metastatic setting albeit with different fractionation regimens. While 68.2% of respondents recommended chemo-radiation and brachytherapy, 31.8% considered additional systemic therapy. Overall 77.3% centers recommended the use of stereotactic ablative radiation therapy to oligo-metastasis. For out-of-field nodal recurrences, 63.7% of respondents considered treating with curative intent, while 59% preferred treating in-field recurrence with palliative intent. A vast majority of the participating centers (90%) have stereotactic radiation therapy capacity and would consider a clinical trial addressing oligo-metastatic and oligo-recurrent cervical cancer. Conclusion: Although contemporary practice is variable, a substantial proportion of EMBRACE centers consider high dose radiation in de-novo metastatic and oligo-recurrence settings. However, there is clear need for a joint clinical protocol and prospective studies to address the role of high dose radiation within oligo-recurrent and oligo-metastatic scenarios.